Strategi Pendidikan Kesehatan pada Ibu Hamil di Masa Pandemi - Hasnah Hasnah; Nurhidayah Nurhidayah; Nurul Fadhilla Gani; Risnah Risnah; Arbianingsih Arbianingsih; Huriati Huriati; Eka Hadrayani; Maria Ulfah Azhar; Muthaharah Muthaharah (STIKes Hang Tuah Pekanbaru, 2021)
The health of pregnant women will determine for health status of the baby. This is also a main concern for the government. Pregnant women bring prospective future generations to the nation who will productively contribute greatly to the progress of the nation. The importance of maternal health can be seen from the government’s policy that the reduction of the Maternal Mortality Rate (MMR) is one of the SDG’s 2030 targets and an indicator of the success of national development. Pregnant women are a vulnerable group, especially in pandemic situations and conditions. Various efforts were made to maintain the health of mothers and babies during pregnancy until delivery. Gowa Regency is a district with the second highest number of Covid case in South Sulawesi. Therefore, it became the basis for implementation of community service in the working area of ​​the Bajeng Public Health Center, Gowa Regency. The method used is to provide health education in the form of a gallery walk with the aim of increasing the knowledge of pregnant women in order to maintain their health. Various important themes in this counseling include: anemia in pregnant women, the risk of 4T in pregnant women, recognizing the symptoms and danger signs in pregnancy, stress management for pregnant women, and nutrition needed by pregnant women and continuing to carry out pregnancy check-up during the pandemic period. During the activities, pregnant women were enthusiastically paying attention to each material provided and actively discussing. At the end of the counseling, we immediately evaluated the knowledge of pregnant women regarding in the materials that had been given. They were very happy with these activities, and looking forward to such activities next time. Therefore, we suggest to related parties, namely the head of the public health center and health workers, to continue to carry out health education regularly and to reactivate the integrated healthcare center for pregnant women during the COVID-19 pandemic period while still implementing health protocols. ABSTRAK Kesehatan ibu hamil merupakan perhatian besar bagi pemerintah. Ibu hamil, membawa calon generasi penerus bangsa yang secara produktif akan berkontribusi besar terhadap kemajuan bangsa dan negara. Pentingnya kesehatan Ibu, dapat dilihat dari kebijakan pemerintah yang menjadikan penurunan Angka Kematian Ibu (AKI) sebagai salah satu target SDG’s 2030 dan indikator keberhasilan pembangunan nasional. Ibu hamil adalah kelompok rentang terlebih disituasi dan kondisi pandemic. Berbagai upaya dilakukan untuk tetap menjaga kesehatan ibu dan bayinya selama proses kehamilan sampai persalinan. Kabupaten Gowa merupakan kabupaten dengan jumlah kasus covid tertinggi kedua di Sulawesi Selatan, maka ini menjadi dasar pelaksanaan pengabdian masayarakat di wilayah kerja Puskesmas Bajeng Kabupaten Gowa. Metode yang digunakan adalah memberikan penyuluhan kesehatan dalam bentuk gallery walk dengan tujuan meningkatkan pengetahuan ibu hamil agar mampu tetap menjaga kesehatannya. Berbagai tema penting pada penyuluhan ini antaralain: anemia pada ibu hamil, resiko 4T pada ibu hamil, mengenal tanda-tanda bahaya kehamilan, manajemen stress pada ibu hamil, dan nutrisi yang dibutuhkan ibu hamil serta tetap melakukan pemeriksaan kehamilan selama pandemic. Selama kegiatan berlangsung para ibu hamil antusias memperhatikan setiap materi yang diberikan dan aktif berdiskusi. Diakhir penyuluhan kami evaluasi secara langsung terkait pengetahuan ibu hamil tentang materi-materi yang sudah diberikan. Mereka sangat senang dengan adanya kegitan ini, dan berharap akan ada kegiatan lanjutan. Maka dari itu kami menyarankan kepada pihak-pihak terkait yaitu kepala puskesmas dan para tenaga kesehatan untuk tetap melaksanakan penyuluhan kesehatan rutin dan kembali mengaktifkan posyandu ibu hamil di masa pandemic covid 19 dengan tetap menerapkan protocol kesehatan.